KONFIGURASI RUANG SIMBIOSIS PERMUKIMAN DI TEPIAN SUNGAI JENEBERANG, MAKASSAR - Andi Annisa Amalia (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Coastal areas are areas of community settlement development that have culturally become part of their living space and livelihoods. Communities that depend on the sea and rivers for their livelihoods tend to choose to settle near or directly integrated with waters. The interconnection and interdependence between urban settlements and water bodies are consistently characterized by the configuration of symbiotic spaces, Symbiotic spaces are manifestations of the results of stimulation by the existence of interactions between spaces. The Jeneberang Riverbank Settlement of Tanjung Merdeka Village Makassar has an unplanned spatial configuration, resulting in the existence of indigenous people's residential areas that are separated from the regional space system. On the other hand, the transformation of the Tanjung Bunga and Centre Point of Indonesia areas as a global business area is an opportunity for coastal communities to utilize the Jeneberang riverbank area as a source of livelihood that leads to a blue economy. This phenomenon has implications for the formation of symbiotic space The research objective is to explore the symbiotic spatial configuration of settlements on the banks of the Jeneberang River in Makassar City. The research method used is a case study with a rationalistic qualitative paradigm approach. The results found that (1) Symbiotic space configuration is formed as a spatial interaction between elements of residential space and livelihood space forming an organic pattern; (2) Symbiotic space configuration forms a floating pattern on the river, radial pattern, cluster pattern, linear pattern, and follows the shape of the footprint of residential outdoor space; (3) Livelihood space as an element of activity support for the area as well as the edge of the riverbank; (4) Transformation of the river's role as a lake affects the spatial order, both in the estuary, riverbank and land area as well as the coexistence of coastal economic livelihood space bound to the waters.